PEMBINA SEBAGAI SAHABAT: KONSTRUKSI KEPEMIMPINAN SAHABAT DI STASI SANTO POLYKARPUS PANDUMPASAN - Pelta Ginting; Herlinda Naibaho (Diegesis : Jurnal Teologi, 2024)
This study addresses the issue of subordination within the servant leadership model and proposes the concept of friendship leadership, which emphasizes an egalitarian relationship between leaders and congregation members, based on the theology of friendship from John 15:15. The objective of the research is to examine the application of the friendship leadership model by OMK mentors at Stasi Santo Polykarpus Pandumpasan and its impact on the active participation of OMK in the Sunday Word service, as well as the improvement of relationships between mentors and OMK. The research argues that the friendship leadership model creates an inclusive environment that supports the spiritual and social growth of the congregation. The qualitative research method employs techniques such as interviews, observations, documentation, and thematic data analysis. The study's findings indicate that the friendship leadership model effectively increases the active participation of OMK, improves the relationships between mentors and OMK, and creates a more inclusive and supportive environment within the church community.